Implementasi Metode Prototyping pada Aplikasi Pembelajaran Metode Tikrar Dalam Menghafal Al-Quran Berbasis Android - Juarsyah, Muhammad; Ikhwan, Ali; Alda, Muhamad (Jurnal Manajemen Informatika JAMIKA, 2025)
In this modern era, technology is increasingly sophisticated and developing, which can be used to facilitate various learning activities. However, there are several obstacles faced by a person who is in the process of memorizing the Qur'an. One of the problems is not often repeating verses that are being or have been memorized. The purpose of this research is to build a Tikrar Method Learning application that can be used to learn materials about the tikrar memorization method through the features and menus contained in the application. The app can also help in testing memorization with a memorization testing feature that utilizes Google Speech API technology. The type of approach used in this study is a qualitative approach consisting of observation, interviews, and literature studies. And the system development method used is the prototyping method. The software used in building the application consists of the codeular framework, google sheets and google script. The result of this research is an application that applies the tikrar method feature in memorizing the Quran along with the memorization testing feature by applying Google Speech API to the application. The advantage of the tikrar method feature in the application is that it can display notifications regarding whether the verses being memorized can be deposited or not and display notifications regarding whether the verses tested through the application already have the correct tajweed or not based on the readings spoken by the user.